Phytoremediation Potential of Maná-Cubiu (Solanum sessiliflorum Dunal) for the Deleterious Effects of Methylmercury on the Reproductive System of Rats. (19th March 2014) - Frenedoso da Silva, Raquel; Missassi, Gabriela; dos Santos Borges, Cibele; Silva de Paula, Eloísa; Hornos Carneiro, Maria Fernanda; Grotto, Denise; Barbosa Junior, Fernando; De Grava Kempinas, Wilma
Abstract : Methylmercury, organic form of mercury, can increase the number of abnormal sperm and decrease sperm concentration and testosterone levels possibly due to the damage caused by reactive species to germ and Leydig cells. Maná-cubiu ( Solanum sessiliflorum Dunal) is a native fruit from Amazon rich in iron, zinc, niacin, pectin, and citric acid, used in foods, beverages, and medicinal purposes, since it has been useful for treatment of various diseases caused by oxidative stress or nutritional deficiency. Therefore, this study evaluated the phytoremediation potential of this fruit on damages caused by exposure to MeHg on sperm quantity and quality and the histological aspect of the testis and epididymis. Wistar male rats (n = 20 ) were randomly allocated into four groups: Control group (received distilled water), MeHg group (140 μ g/Kg), Solanum group (1% of fruit Maná-cubiu on chow), and Solanum plus MeHg group (same treatment as MeHg and Solanum group). The organs were weighted, histopathology; sperm morphology and counts were obtained. The results showed reduction in body weight gain, testis weights, reduced sperm production, and increased histopathological abnormalities in the MeHg-treated group. However, treatment with Solanum plus MeHg revealed a protective effect of this fruit on damages caused by MeHg.